microRNA expression profile in porcine oocytes with different developmental competence derived from large or small follicles - Gad, Ahmed; Nemcova, Lucie; Murin, Matej; Kanka, Jiri; Laurincik, Jozef; Benc, Michal; Pendovski, Lazo; Prochazka, Radek (Wiley, 2019)
Oocyte developmental competence is acquired during folliculogenesis and regulated by complex molecular mechanisms. Several molecules are involved in these mechanisms, including microRNAs (miRNAs) that are essential for oocyte-specific processes throughout the development. The objective of this study was to identify the expression profile of miRNAs in porcine oocytes derived from follicles of different sizes using RNA deep sequencing. Oocytes were aspirated from large (LO; 3-6 mm) or small (SO; 1.5-1.9 mm) follicles and tested for developmental competence and chromatin configurations. Small RNA libraries were constructed from both groups and then sequenced in an Illumina NextSeq. 500. Oocytes from the LO group exhibited higher developmental competence and different chromatin configuration compared with oocytes from the SO group. In total, 167 and 162 known miRNAs were detected in the LO and SO groups, respectively. MiR-205, miR-16, miR-148a-3p, and miR-125b were among the top 10 highly expressed miRNAs in both groups. Eight miRNAs were differentially expressed (DE) between both groups. Target gene prediction and pathway analysis revealed 46 pathways that were enriched with miRNA-target genes. The oocyte meiosis pathway and signaling pathways including FoxO, PI3K-Akt, and cAMP were predictably targeted by DE miRNAs. These results give more insights into the potential role of miRNAs in regulating the oocyte development.